KURUMSALLAŞMA İŞLETME İLE MÜŞTERİ ARASINDA BARİYER Mİ? (MÜCEVHER SEKTÖRÜNDE BİR ARAŞTIRMA) - (:unkn) unknown (My University, 2016)
İşletmeler küresel arenada üstün konumlarını devam ettirmek için sürekli büyümek istemektedirler. Büyürken işlerin karmaşıklaşması, organizasyon yapısının hantallaşması, çalışanların iş tanım ve analizlerinin belirsizliği gibi sorunlarla karşılaşılabilir. Kurumsallaşma, işlerin standartlara bağlanması ve profesyonelleşmesi sonucunda işletmelerin bu sorunlarını aşmalarına yardımcı olmaktadır. Kurumsallaşmak isteyen birçok işletme özellikle sürdürülebilirlik konusunda birinci kuşaktan sonra ikinci ve üçüncü kuşakların yönetiminde de işletmenin başarıyla hayatta kalmasını arzular. Kurumsallaşma ile işletmenin varlığı yönetim kurulu başkanının varlığı ile sınırlı olmaktan çıkar. Kurumsallaşmanın işletmelere getirmiş olduğu birçok avantaj vardır. Ancak kurumsallaşma sürecini uygulamak ve hayata geçirmek oldukça zordur. Aynı zamanda kurumsallaşan birçok işletme prosedürlerini ve müşteri ile olan ilişkilerini yeniden düzenlemek durumundadırlar. Araştırma kurumsallaşan ya da bu sürece giren işletmelerde, müşteri ile işletme arasındaki yeni düzenlemeleri ve getirdiği sonuçları işletme açısından ele almış, kurumsallaşmanın etkilerini farklı bir perspektiften değerlendirmiştir. Çalışmanın amacı kurumsallaşan firmaların eski ve yeni iş tarzları arasındaki farkı görebilmektir. Bu amaçla da kuyumculuk sektöründe faaliyette bulunmuş bir firmanın kurumsallaşmadan önceki çalışma tarzı ve iş yapma alışkanlıkları ile kurumsallaştıktan sonraki iş yapma tarzı -müşteri- ile ilişkiler açısından karşılaştırılmıştır. Firmanın yaklaşık olarak 13 yıllık bir dönemi incelenmiştir. Araştırma görgül bir çalışmadır. Araştırmada bulgular firmanın yönetim kurulu başkanı ve 13 yıldır sürekli olarak çalışan üst düzey yöneticileri de dahil olmak üzere derinlemesine görüşme yapılarak incelenmiş ve sonuçlar analiz edilmiştir.

Businesses always need to grow continuously to maintain their superior position in the global arena. Problems as the complexity of the growing businesses, the cumbersomeness of organizational structure, and the uncertainty of the job description and the employees analysis can be encountered. Institutionalization helps businesses to overcome the problems resulted from the standards limitations and and professionalization. Many enterprises seeking to be institutionalized wish the enterprise to survive successfully especially in the second and third generations in terms of sustainability. The entity's existence will no longer be limited to the existence of the chairman of the board with the institutionalization. There are so many advantages in bringing the institutionalization into the businesses. But it is difficult to apply the institutionalization process and make it happen in the real life. At the same time, many institutionalized business procedures and their relationships with the customer must also be reorganized. The research has taken into account the new arrangements between the customer and the business and the results they have brought from the business perspective and evaluated the effects of the institutionalization from a different perspective in the enterprises that are institutionalized or prepared to enter this process. As it is well known, institutionalisation means the standardisation of the works in brief. It is expected that the lifetime of the institutionalized companies are not to be limited by the lifetime of it's owner or founder. The workload will be detailed to the utmost extent and each kind of work will be conducted professionally. This study's aim is to perceive the difference between the old and new work styles of the institutionalised companies. For this purpose, the work style and business habits of a company which used to operate in jewelry sector were compared with it's new work style as an institutionalised company. Approximately, a term of 13 years of the company were analyzed. The research is an empirical study. In the research, the symptoms and results were obtained by in depth interviews with the chairman of the company and the staff, which have been working for 13 years, and analyzed thus.
Institutionalization is a Barrier between the Firm and Its Customers (A Research in Jewellery Sector)?